2020
DOI: 10.22271/j.ento.2020.v8.i4ai.7462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of Garlic (Allium sativum) and turmeric (Curcuma longa) powder on growth and nutrient utilization of female crossbred calves during winter season

Abstract: Submission of an original paper with copyright agreement and authorship responsibility.I (corresponding author) certify that I have participated sufficiently in the conception and design of this work and the analysis of the data (wherever applicable), as well as the writing of the manuscript, to take public responsibility for it. I believe the manuscript represents valid work. I have reviewed the final version of the manuscript and approve it for publication. Neither has the manuscript nor one with substantial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Among these measures, curcumin supplementation is a safe and nontoxic solution, making it more attractive to scientists compared to other phytogenic compounds [66]. Turmeric-powder addition has been shown to enhance nutrient utilization in female calves during the winter season [67]. Furthermore, Hameed et al [65] indicated that turmeric extract (100 µL/5 mL and 200 µL/5 mL) could improve the quality of cooled and post-thawed cattle bull semen.…”
Section: Thermal Stress Managementmentioning
confidence: 99%
“…Among these measures, curcumin supplementation is a safe and nontoxic solution, making it more attractive to scientists compared to other phytogenic compounds [66]. Turmeric-powder addition has been shown to enhance nutrient utilization in female calves during the winter season [67]. Furthermore, Hameed et al [65] indicated that turmeric extract (100 µL/5 mL and 200 µL/5 mL) could improve the quality of cooled and post-thawed cattle bull semen.…”
Section: Thermal Stress Managementmentioning
confidence: 99%